Hukum yang Hidup dalam Perspektif Filsafat Hukum dan Syariah: Rekonstruksi Pengembangan Hukum Islam Kontemporer - Mulyadi Mulyadi; Ahmadi Hasan; Sukarni Sukarni (Interdisciplinary Explorations in Research Journal, 2026)
This article examines the construction of living law from the perspectives of legal philosophy and Islamic law as an instrument for reconstructing the development of contemporary Islamic law in Indonesia. The increasing complexity of contemporary Muslim societies has widened the gap between formal legal norms and rapidly evolving social realities. This study aims to analyze the concept of living law from the perspective of legal philosophy, explore its relationship with the doctrines of ‘urf, ijtihad, and maqāṣid al-sharī‘ah within the Islamic legal tradition, and formulate a conceptual model that integrates these perspectives for the development of contemporary Islamic law. This research employs a normative legal research design using doctrinal, conceptual, philosophical, and comparative approaches through the analysis of both classical and contemporary legal literature. The findings reveal that living law in the Islamic legal tradition is not merely a form of social custom recognized by law. Rather, it functions as an epistemological instrument that connects social realities with the objectives of the Sharī‘ah. The integration of legal-philosophical and Islamic legal perspectives produces a model of Islamic legal development that is adaptive, responsive, and oriented toward public welfare while maintaining its normative authenticity. This article proposes a Living Law-Based Islamic Legal Reconstruction Model that integrates legal philosophy, maqāṣid al-sharī‘ah, ‘urf, and ijtihad into a unified framework for the development of contemporary Islamic law. The proposed model offers a theoretical foundation for bridging the divide between legal formalism and social realities, thereby enhancing the capacity of Islamic law to respond effectively to contemporary societal challenges.